International Editorial Board of vol. 18, 2020, Journal Scientific and Applied Research: International Editorial Board of vol. 18, 2020, Journal Scientific and Applied Research - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
International Editorial Board of vol. 18, 2020, Journal Scientific and Applied Research